OFF THE JOB DISCRIMINATION BY EMPLOYERS AGAINST SMOKERS (Tufts Archival Research Center, 2007)
Draft; 1995 Draft of a report entitled “Off the job discrimination by employers against smokers” reporting on the issue of discrimination based on smoking during and after work hours. Compares smoking discrimination with other types, such as discrimination based on obesity, alcohol and genetic make-up. Cautions that more civil liberties will disappear if such discrimination is allowed.